After the Honeymoon: Neural and Genetic Correlates of Romantic Love in Newlywed Marriages - Acevedo, Bianca P.; Poulin, Michael J.; Collins, Nancy L.; Brown, Lucy L. (Frontiers in Psychology, 2020)
Romantic love is associated with relationship satisfaction, stability, and individual well-being. For many couples, romantic love also motivates marriage. An overall hypothesis is that romantic love is a developed form of the mammalian drive to pursue, and keep, preferred mates. Here, we predicted that neural, hormonal, and genetic correlates of pair-bonding found in humans and other mammals, including the reward/drive system activated in human love studies, would be involved in the maintenance of romantic love over the first year of marriage. We measured self-report (Eros scale) and neural (functional MRI) correlates of romantic love among first-time newlyweds around the time of the wedding (T1) and one year after (T2). Romantic love maintenance (Eros difference score: T2-T1) for each individual was correlated with brain activations at both T1 and T2. Additionally, for the first time in romantic love studies, we analyzed interactions between brain activation and genetic polymorphisms of hormone receptors and dopamine functions involved in mammalian pair-bonding (AVPR1a rs3, OXTR rs53576, COMT rs4680 and DRD4-7R). At both time points, romantic love maintenance was associated with activation of the dopamine-rich substantia nigra in response to face images of the partner. Also, the reward system’s ventral tegmental area showed significant interactions with AVPR1a rs3, OXTR rs53576, COMT rs4680 and DRD4-7R, and romantic love maintenance at both time points. The paracentral lobule (genital region) and other cortical areas involved in sensory and cognitive processing (occipital, angular gyrus, insular cortex) were also associated with romantic love maintenance, corroborating evidence implicating sexual intimacy in romantic love. These results suggest that romantic love, and its maintenance, are orchestrated by the mammalian dopaminergic reward system, as well as vasopressin and oxytocin receptors used by other mammals for pair-bonding. Our findings also suggest, for the first time, that genetic polymorphisms underlying oxytocin, vasopressin and dopamine function may influence romantic love maintenance during the first year of marriage. We conclude that in any one individual romantic love maintenance is part of a broad mammalian strategy influenced by basic drives, hormones, and complex cognitive and genetic processes.